2017
DOI: 10.1002/2016jc012527
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between optimal precursors for Indian Ocean Dipole events and optimally growing initial errors in its prediction

Abstract: Using the Geophysical Fluid Dynamics Laboratory Climate Model version 2p1, we explored the precursory disturbances that are most likely to develop into a positive Indian Ocean Dipole (IOD). The dominant spatial patterns of these precursors are defined as the optimal precursors (OPRs) of positive IOD as they are more inclined to cause a positive IOD than other superimposed initial perturbations in the experiments. Specifically, there are two types of OPRs with opposite patterns; the surface component of OPR‐1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…While these precursors explain some of the IOD events, predicting IOD event is still challenging. Above all, how to overcome the so‐called “winter predictability barrier” is still a problem (Feng et al, 2017; Mu et al, 2017; Wajsowicz, 2005). However, the 2019 event was successfully predicted using the SINTEX‐F system over the winter predictability barrier; it is of interest to study why the barrier was overcome.…”
Section: Introductionmentioning
confidence: 99%
“…While these precursors explain some of the IOD events, predicting IOD event is still challenging. Above all, how to overcome the so‐called “winter predictability barrier” is still a problem (Feng et al, 2017; Mu et al, 2017; Wajsowicz, 2005). However, the 2019 event was successfully predicted using the SINTEX‐F system over the winter predictability barrier; it is of interest to study why the barrier was overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already revealed that optimally designed observations can result in better prediction performance than conventional observations (Alvarez and Mourre, 2012;Li et al, 2014). By using the CNOP approach, our group has also optimized the observation designs to improve the predictions of high-impact ocean-atmospheric extreme events (Mu et al, 2007;Yu et al, 2012;Wang et al, 2013;Mu et al, 2017;Liu et al, 2018;Zhang et al, 2019). In these studies, the optimal observation locations are different for predicting and mapping the same phenomenon.…”
Section: Observation Design For Both Understanding and Forecasting Thmentioning
confidence: 99%
“…It has been found that the IOD has significant impacts on global weather and climate (Blau & Ha, 2020; Chan et al., 2008; Ratna et al., 2021; Saji & Yamagata, 2003). Targeted observation analysis for SST associated with the IOD has been reported in the literature, but only using the first approach described above; for example, the perfect model predictability experiments (Feng et al., 2017), and the conditional nonlinear optimal perturbation (Mu et al., 2017). Therefore, it is of interest to conduct similar analyses of targeted observations using a different method, shedding light on the robustness of previously reported results.…”
Section: Introductionmentioning
confidence: 99%